Cool-SPS: an opportunity for low temperature sintering of thermodynamically fragile materials. Issue 9 (21st February 2018) - Herisson de Beauvoir, Thomas; Sangregorio, Anna; Cornu, Iñaki; Elissalde, Catherine; Josse, Michael
Abstract : Sintering has been achieved by Spark Plasma Sintering at low temperatures (<400 °C) and relatively high pressures (300 to 600 MPa) for various thermodynamically fragile compounds (carbonates, sulfate, and phosphate) decomposing between 220 and 780 °C. Abstract : Sintering has been achieved by Spark Plasma Sintering at low temperatures (<400 °C) and relatively high pressures (300 to 600 MPa) for various thermodynamically fragile compounds (carbonates, sulfate, and phosphate) decomposing between 220 and 780 °C. Our work is a proof of concept of the possibility to sinter efficiently (>90% of theoretical density) fragile materials, and also highlights the extra stability afforded by this approch for certain materials which have been sintered above their normal decomposition temperature. Using multiple examples, this work illustrates the potential of "Cool-SPS" for fast and efficient sintering of fragile materials which are impossible to sinter by conventional sintering techniques.